Optimizing insecticide application for effective fall armyworm (Spodoptera frugiperda) management in Sorghum: a field study on spray frequency and rates - Aderajew Mihretie; Admasie Kassaw; Abebe Ayalew; Abate Abtie; Abiye Tiruneh; Mequanint Andualem Mekonnen (Discover Agriculture)
Abstract A field experiment was conducted to assess the impact of spray frequency and application rates of Agro-lambacin (Agro-lambacin Super 315 EC, containing profenfos 30% and lambda-cyhalothrin 1.5%) insecticide on the management of Fall Armyworm (Spodoptera frugiperda) in Sorghum. The study evaluated foliar application rates of 0.2 L ha⁻1, 0.4 L ha⁻1, and 0.6 L ha⁻1, with application frequencies of once, twice, and thrice, alongside an untreated control. This was carried out at the Sirinka and Kobo sites using a randomized complete block design with three replications during the main cropping season of 2020 (July to November). Fall armyworm (FAW) larval infestation, foliar damage, Sorghum head weight, and overall yield were recorded. Results indicated significant variations across treatments. Notably, the three-time application of 0.6 L ha⁻1 and 0.4 L ha⁻1 consistently resulted in lower mean larval populations per plant and reduced foliar damage throughout the cropping season. These treatments also yielded higher grain yield, with percentage yield increases of 29.47% and 20.76%, respectively, compared to the untreated control at Kobo. In contrast, while treatment effects were evident at Sirinka during the spray regimes, the yield did not reflect this due to ongoing infestations after the completion of the spray applications. Therefore, a three-times application of Agro-lambacin, starting approximately 22 days after planting at ten-day intervals, using the manufacturer's recommended rate of 0.4 L ha⁻1 or an increased rate of 0.6 L ha⁻1, is deemed effective and economically viable for Kobo and similar areas. However, for Sirinka, further research is necessary to explore the optimal spray sequence or total number of applications required for effective management of FAW in Sorghum.